Strategi Branding dan Komunikasi Politik Anies Baswedan melalui Instagram dalam Pemilu 2024 - Widiantoro, Aries (Jurnal Inovasi Komunikasi, 2025)
This research is motivated by the rapid development of social media as a tool for political communication, particularly Instagram, which is used by politicians to build their image, convey political messages, and interact with voters. Anies Baswedan, as one of Indonesia's prominent political figures, actively uses Instagram to express ideas and engage with the public. In the context of digital politics, understanding political communication styles on social media is crucial to understanding how messages are delivered and their impact on voters. This study aims to analyze Anies Baswedan’s political communication style on Instagram, including the use of visual content, text, hashtags, and audience interaction. The research method employed is qualitative with a case study approach, in which data is collected through content analysis of Anies Baswedan’s Instagram posts. This approach enables an in-depth understanding of the communication strategies applied. The results show that Anies Baswedan employs a persuasive and personal political communication approach, relying on engaging visuals, strong narratives, and the use of relevant hashtags to boost audience engagement. Additionally, he utilizes Instagram features such as Stories and Live to foster closeness with voters. His communication tends to reflect an intellectual, visionary, and down-to-earth leadership image. The conclusion of this study is that Instagram serves as an effective tool for Anies Baswedan in shaping his political image and interacting with voters. The communication style applied demonstrates how social media can be leveraged to enhance political appeal and build relationships with the public. These findings are expected to provide insights for other politicians in optimizing their political communication strategies in the digital era.